Aetiological factors and clinical profile of neonatal jaundice from a rural area of North Kerala, India - Valiyat, Shemeena; Valoor, Harsha T.; Radhamadhavan, Sayujya; Vayalil, Salina Sasi (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal jaundice is the most common problem in the first week of life leading to delayed hospital discharge and readmissions. Early recognition of neonatal hyperbilirubinemia is important to prevent serious complications. This study was done in a teaching hospital (KMCT Medical College, Mukkam, Kozhikode), in a rural area of North Kerala. It is an attempt to identify the common aetiological factors of neonatal jaundice in this setting. Methods: This observational study was conducted over a period of 6 months from January 2014 to June 2014. A total of 110 jaundiced neonates were enrolled. Data collection was done by history taking, clinical examination and relevant laboratory investigations. Results: In this study, out of 110 jaundiced neonates, 102 (92.5%) were term babies and 8 (7.3%) were preterm, 69 (62.75%) were males and 41 (37.27%) females. Physiological jaundice was seen in 44 (40%) of neonates. Various other aetiologies were ABO incompatibility 24 (21.8%), sepsis 11 (10%), Rh incompatibility 9 (8%), idiopathic 9 (8%), prematurity 8 (7.3%), cephalhematoma 7 (6.4%), breast feeding jaundice 7 (6.4%) and haemolytic anaemia 1 (0.9%). Conclusions: Physiological jaundice accounted for the bulk of cases of neonatal jaundice in our area. This was followed by ABO incompatibility. This highlights the importance of appropriate monitoring of neonates with this underlying risk factor.